CYBERBULLYING ANAK AKIBAT OVERSHARENTING DIGITAL: BATASAN OTORITAS PERWALIAN PERSPEKTIF MAQASHID SYARI’AH - Endiana Silviani (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study aims to reconstruct the boundaries of parental guardianship rights over children's privacy in the digital space based on the Maqashid Sharia perspective. Using a qualitative socio-legal method, a conceptual approach, and netnography, this study observes three YouTube accounts of public figure families (